Pengembangan Sistem Kelistrikan Motor Brushless Direct Current Speed Uwp V2.2 Kapasitas 2000 Watt - Purnama, Robertus Bayu; Pangestu, Moh Aji Surya; Pamungkas, Achmad Aji; Bukhori, Muhammad Rizaldi; Riyadi, Slamet (Journal of System Engineering and Technological Innovation, 2022)
This final project aims to realize an environmentally friendly and fuel-efficient vehicle. The increasing need for fuel oil causes several obstacles to the use of oil; for that, one way to overcome the limitations and dependence on fuel is the use of vehicles with electric energy. One solution is to use electrical energy as a source of electrical energy in transportation such as electric cars, electric motorcycles, electric trains, and many others. The electrical system has an important role in the comfort and safety of the driver of the DC motor, lithium battery, and controller as the main components. In finding the maximum load for the rider on the bicycle, 250 kg is obtained. Electric bicycles can go up to a maximum speed of 90 km/h. Furthermore, cover the maximum distance with a full battery charge of 40 km. The 72V-30Ah battery can safely drive an electric motor powered by a 2000 watt motor and a rotational speed of 1000 rpm.